Pengaruh Metode Penyayatan dan Kedalaman Penyayatan terhadap Dimensi dan Kekasaran Permukaan Kayu Olahan - Bahtiar Rahmat; Agung Ari Purwanto; Muhammad Fahrudin; Wahyu Widiyanto (Infotekmesin, 2025)
The application of CNC technology in the furniture industry has already become familiar, in addition to its use in the metal and plastic industries. HMR (High Moisture Resistant) panels, which had better moisture resistance than MDF (Medium Density Fiberboard), had also started to develop. However, few studies have investigated the effects of variations in machining parameters on the cutting quality of HMR boards. This study aimed to test the effects of machining parameters (cutting method and cutting depth) on the dimensions and surface roughness of the workpiece. Four schemes of machining parameter settings, namely conventional and climb methods with cutting depths of 2 mm and 4 mm, respectively, were performed with three repetitions each. After testing, it was found that the cutting method, cutting depth, and the interaction between the cutting method and cutting depth had not significantly affected the length and width dimensions of the specimen. However, the cutting method significantly influenced the final surface roughness of the specimen. The conventional cutting method with a cutting depth of 2 mm produced the best surface roughness, measuring 26.47 Âµm.